Meningkatkan Perilaku Pencegahan Diare pada Anak Usia Sekolah melalui Permainan Terapeutik Wayang Golek Cepak Tegalan - Nur An Nisa Najibah Gumay; Dyah Dwi Astuti; Sunarsih Rahayu (Faletehan Health Journal, 2025)
Diarrhoea is the leading cause of death among children both globally and nationally, can be prevented through therapeutic play using local cultural approaches such as wayang golek cepak tegalan (traditional puppet show). Nurses play an important role as health educators in improving diarrhea prevention behaviours among school-aged children through the play. This study aimed to analyse the effects of wayang golek cepak tegalan therapeutic play on diarroea prevention behaviours among school-aged children. The research design was pre-experimental with a one-group pre- and post-test design without a control group. The sampling technique used was purposive sampling with a sample size of 38 school-aged children. The research instruments were questionnaires and observation sheets on diarrhea prevention behaviour, which included knowledge, attitudes, and practices. Data analysis used a paired sample t-test. The results showed that the average score for children's behaviour before the intervention was 62.11, while after the intervention was 84.82 with a p-value <0.001. There was an effect of therapeutic play with wayang golek cepak tegalan on diarrhea prevention behaviour among school-age children. Nurses can apply the therapeutic play of wayang golek cepak tegalan to improve diarrhoea prevention behaviour in school-aged children.